Formulasi dan Uji Mutu Fisik Sediaan Body Scrub dari Arang Aktif Sekam Padi (Oryza sativa): Formulation and Physical Quality Test of Provision of Body Scrub from Rice Husb Active Character (Oryza sativa) - Chelsie Onesya Prolapita; Cikra Ikhda Nur Hamida Safitri (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Rice husk (Oryza sativa) has a high content of activated carbon, activated charcoal is able to open clogged pores and improve skin cleansing by removing dead skin on the surface. Activated charcoal rice husk formulated sebagai scrubs using stearic acid, cethyl alcohol, and propilenglikol. Scrub as a scrub to remove dead skin cells using amylum oryzae. The concentration of activated rice husk charcoal used was 0% in the control formula, 8 % in formula I, 10% in formula II, and 12% in formula III. Evaluation Physical quality of body scrub based on parameters such as organoleptic, homogeneity test, pH test, spreadability test, adhesion test, emulsion type test. Body scrubs activated charcoal rice husk has a stable pH 7. Dispersibility formulation is 5,7cm, 5,8cm, 5,6cm. Rice husk activated charcoal body scrub is stable in room temperature storage or low temperature (2-8?C). All formulations evenly distributed homogeneously have stable color, smell and taste. Rice husk activated charcoal (Oryza sativa) can be formulated into a stable body scrub that meets the requirements. The most stable formulation was formulation 1 with a concentration of rice husk activated charcoal (Oryza sativa) of 8%.